Recurrent proliferating pilar tumour of the scalp mimicking squamous cell carcinoma successfully treated surgically using S-plasty - Męcińska-Jundziłł, Kaja; Białecka, Agnieszka; Adamska, Urszula; Cieścińska, Czanita; Jundzill, Arkadiusz; Witmanowski, Henryk; Neska-Długosz, Izabela; Grzanka, Dariusz; Czajkowski, Rafał (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
Pilar cysts often occur within the scalp. As they arise from the trichilemma or outer root sheath, they are called “trichilemmal cysts” (TCs). In 1966, Wilson-Jones reported uncommon lesions developing from TCs called proliferating pilar tumours (PPTs) which histologically simulated squamous cell carcinoma [1]. PPTs may develop de novo as well [2]. They usually occur on the scalp with a predilection for women [3]. The histological characteristic is trichilemmal-type keratinization [4]. They may be benign, locally aggressive or malignant [5]. In the literature we can find other terms describing these lesions as subepidermal acanthoma, proliferating trichilemmal cyst, invasive hair matrix tumour, invasive pilomatrixoma, proliferating epidermoid cyst, hydatidiform keratinous cyst, giant hair matrix tumour, trichochlamydoacanthoma or pilar cysts and tumours, what is consistent with their ambiguous biological nature [4–6]. We report a case of recurrent PPT of the scalp mimicking squamous cell carcinoma successfully treated surgically using S-plasty with a satisfying aesthetic effect.